Does the sympathetic nervous system contribute to the pathophysiology of metabolic syndrome? - Moreira, Marina C.; Pinto, Izabella S.; Mourão, Aline A.; Fajemiroye, James O.; Colombari, Eduardo; Reis, Ângela A.; Freiria-Oliveira, André H.; Ferreira-Neto, Marcos L.; Pedrino, Gustavo R. (Frontiers in Physiology, 2015)
The metabolic syndrome (MS), formally known as syndrome X, is a clustering of several risk factors such as obesity, hypertension, insulin resistance and dislypidemia which could lead to the development of diabetes and cardiovascular diseases (CVD). The frequent changes in the definition and diagnostic criteria of MS are indications of the controversy and the challenges surrounding the understanding of this syndrome among researchers. Obesity and insulin resistance are leading risk factors of MS. Moreover, obesity and hypertension are closely associated to the increase and aggravation of oxidative stress. The recommended treatment of MS frequently involves change of lifestyles to prevent weight gain. MS is not only an important screening tool for the identification of individuals at high risk of CVD and diabetes but also an indicator of suitable treatment. As sympathetic disturbances and oxidative stress are often associated with obesity and hypertension, the present review summarizes the role of sympathetic nervous system and oxidative stress in the MS.